Analisis Aktualisasi Manajemen Peningkatan Mutu Berbasis Madrasah - Muhammad Asrori Ma’sum (Realita: Jurnal Penelitian dan Kebudayaan Islam, 2017)
Islamic education in Indonesia extremely urgent to be examined because citizen of Indonesia are mostly moslem, until it become education progression factor in a country with mostly moslem citizen. The entrance used to collect empirical and actual data in order to critically analyzed quality management theory which is islamic education like madrasah. Madrasah as formal islamic education organization that integrated within national education system in Indonesia needs quality management. Madrasah based quality advance management is a management model that extend bigger autonomy to madrasah, giving flexibility to madrasah, and encourage direct participation from stakeholders to increase the quality of madrasah.